2019
DOI: 10.3390/ijerph16203890
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients with Acute Myocardial Infarction (AMI) in Pakistan: A Retrospective Study

Abstract: A wide variation exists in the practice patterns of acute myocardial infarction (AMI) care worldwide, leading to differences in clinical outcomes. This study aims to evaluate the quality of process care and its impact on in-hospital outcomes among AMI patients in Pakistan, as no such study has been conducted in Pakistan thus far based upon recommended guidelines. We investigated a sample of 2663 AMI patients across 11 territory hospitals in Punjab province of Lahore, Faisalabad, Multan, Rawalpindi, and Islamab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…CVDs have affected all the income level countries, especially low- and middle-income countries (LMIC) contribute the greatest portion to the overall CVD burden, specifically in terms of deaths at younger ages than in high-income countries, because of scarce human and financial resources [ 11 13 ]. Whereas, several of the largest LMIC had an increase in the overall burden of CVD; in decreasing pattern of percent burden increase, those included: India (15.4%), Bangladesh (27.4%), Indonesia (8.8%), China (6.6%), the Philippine (25.3%), and Mexico (19.7%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…CVDs have affected all the income level countries, especially low- and middle-income countries (LMIC) contribute the greatest portion to the overall CVD burden, specifically in terms of deaths at younger ages than in high-income countries, because of scarce human and financial resources [ 11 13 ]. Whereas, several of the largest LMIC had an increase in the overall burden of CVD; in decreasing pattern of percent burden increase, those included: India (15.4%), Bangladesh (27.4%), Indonesia (8.8%), China (6.6%), the Philippine (25.3%), and Mexico (19.7%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Time is directly proportional to the rates of mortality in patients with acute STEMI, those who receive reperfusion therapy within time are more likely to get benefited as compare to those who do not [9]. While data from national hospitals is still lacking but a study conducted by Rehman S in 2019 in different cities of Punjab (a province in Pakistan) in which they have included all patients with acute myocardial infarction irrespective of STEMI and non-ST elevation myocardial infarction (NSTEMI) has shown the in-hospital mortality rate was 8.6% [10]. This difference in rates of inhospital outcome is possibly due to eligibility criteria of patients as in our study we included high-risk patients who did not receive reperfusion therapy while their studies have included all patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic NCDs, especially CVD, are becoming a serious threat in LMICs, including the densely populated South Asian nations, as a result of fast industrialization, higher survival from acute diseases, and population aging [ 5 ]. NCDs now account for 52 percent of mortality in South Asia, and by 2030, they are expected to account for 72 percent of overall mortality [ 6 , 7 ]. An abundance of evidence has shown that South Asians are at elevated risk of CVDs bringing about calls to upgrade CVD prevention in South Asian nations and migrant populations.…”
Section: Introductionmentioning
confidence: 99%